Secondary prevention of stroke and post-stroke dementia - Pendlebury, S; Rothwell, P (2008)
Stroke remains the second most common cause of death worldwide and the most common cause of neurological disability in the developed world. Progress has been made in the primary prevention of stroke through more aggressive treatment of risk factors, particularly hypertension, resulting in a fall in stroke incidence. However, there is still scope for improvement in secondary prevention, particularly in reducing the high early risk of stroke after transient ischaemic attack (TIA) or minor stroke, and there is a need for a better understanding of the risks and determinants of cognitive impairment and dementia after TIA and stroke. We review several recent studies that have changed the management after TIA and stroke, and briefly consider the evolving concept of stroke-associated cognitive impairment. © 2008 Elsevier Ltd. All rights reserved.